Polishing pad and polishing device

The polishing pad addresses the issue of scratches caused by varying hardness in hollow particles by ensuring uniform elastic modulus distribution, resulting in consistent contact pressure and reduced scratches on polished objects.

JP2025056986APending Publication Date: 2025-04-09FUJIBO HLDG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023166567
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Conventional polishing pads with hollow particles on their surface can cause scratches in polished objects due to variations in hardness of the hollow particles, leading to inconsistent contact pressure.

Method used

A polishing pad with a polishing layer composed of resin and hollow particles, where the elastic modulus of the hollow particles is uniformly distributed, as measured by an atomic force microscope, to minimize variations in contact pressure.

Benefits of technology

The polishing pad effectively reduces the occurrence of scratches on polished objects by ensuring consistent contact pressure across the surface, thereby improving the polishing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056986000001_ABST
    Figure 2025056986000001_ABST
Patent Text Reader

Abstract

To provide a polishing pad and a polishing device which can reduce occurrence of scratch in an object to be polished.SOLUTION: A polishing pad 10 includes a polishing layer 11, wherein the polishing layer 11 contains a resin 11B and hollow particles 11C dispersed in the resin 11B, when in a region of 4 μm×4 μm of an inner bottom part 11C1 of the hollow particles 11C, which is positioned on a surface 11A of the polishing layer 11 and is opened, elastic moduli at 16,384 points are measured by an atomic force microscope, and an elastic modulus histogram with widths of classes of 2 GPa is created, a half-value width of a peak of an approximate curve based on the elastic modulus histogram is 12 GPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad and a polishing apparatus. [Background technology]

[0002] Conventionally, chemical mechanical polishing (CMP) using a slurry and a polishing pad has been used to polish objects such as semiconductor wafers because extremely precise flatness is required for such objects. CMP is a method in which a slurry is supplied to the polishing surface of a rotating polishing pad while pressing the object to be polished, such as a semiconductor wafer, against the polishing pad and rotating the pad to polish the surface of the object.

[0003] It is currently known that hollow particles for holding a slurry are dispersed in the polishing layer constituting a polishing pad (see, for example, Patent Document 1). In the polishing layer containing such hollow particles, the hollow particles are located on the surface of the polishing layer and open, so that the slurry can be held inside the hollow particles, and therefore a large amount of slurry can be held on the surface of the polishing layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7285613 Summary of the Invention [Problem to be solved by the invention]

[0005] However, if the open hollow particles present on the surface of the polishing layer have localized variations in hardness, the contact pressure with the workpiece to be polished will vary, which may result in scratches on the workpiece to be polished.

[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a polishing pad and a polishing apparatus that can reduce the occurrence of scratches on an object to be polished. [Means for solving the problem]

[0007] [1] A polishing pad having a polishing layer, the polishing layer comprising a resin and hollow particles dispersed in the resin, the polishing pad being located on the surface of the polishing layer, and when the elastic modulus is measured at 16,384 points within a 4 μm × 4 μm area at the inner bottom of an open hollow particle using an atomic force microscope and an elastic modulus histogram with a class width of 2 GPa is created, the half-width of the peak of the approximation curve based on the elastic modulus histogram is 12 GPa or less.

[0008] [2] The polishing pad according to [1] above, wherein the peak is in the range of 1 GPa or more and 20 GPa or less.

[0009] [3] The polishing pad according to [1] or [2] above, wherein the frequency of the peak when the elastic modulus is measured at 16,384 points within the region is 2,000 or more.

[0010] [4] The polishing pad according to any one of [1] to [3] above, wherein the surface of the polishing layer has pores formed by openings in the hollow particles, and the average opening diameter of the pores is 5 μm or more and 20 μm or less.

[0011] [5] The polishing pad according to any one of [1] to [4] above, wherein the approximation curve is unimodal.

[0012] [6] The polishing pad according to any one of [1] to [5] above, wherein the resin comprises a polyurethane resin.

[0013] [7] The polishing pad according to any one of [1] to [6] above, wherein the hollow particles have an outer shell, and the outer shell does not contain a polyvinylidene chloride copolymer.

[0014] [8] A polishing apparatus comprising the polishing pad described in any one of [1] to [7] above. Effect of the Invention

[0015] According to the present invention, it is possible to provide a polishing pad and a polishing apparatus capable of reducing the occurrence of scratches on an object to be polished. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic diagram of a polishing pad according to an embodiment. [Diagram 2] FIG. 2 is an enlarged view of a portion of FIG. [Diagram 3] FIG. 3 is a schematic diagram showing a state in which the elastic modulus of the polishing layer of the polishing pad according to the embodiment is measured by an atomic force microscope (AFM). [Figure 4] FIG. 4 is a schematic diagram of a polishing apparatus including a polishing pad according to an embodiment. [Diagram 5] FIG. 5 is a photograph taken when the elastic modulus of the polishing layer of the polishing pad according to Example 1 was measured with an atomic force microscope (AFM). [Figure 6] FIG. 6 is a graph showing approximate curves of elastic modulus histograms obtained by measuring the elastic modulus of the polishing layers of the polishing pads according to Examples 1 and 2 and Comparative Example 1 using an atomic force microscope (AFM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] A polishing pad and a polishing apparatus according to an embodiment of the present invention will be described below. Fig. 1 is a schematic diagram of the polishing pad according to this embodiment, Fig. 2 is an enlarged view of a part of Fig. 1, Fig. 3 is a schematic diagram showing a state in which the elastic modulus of the polishing layer of the polishing pad according to this embodiment is measured by an atomic force microscope (AFM), and Fig. 4 is a schematic diagram of a polishing apparatus equipped with the polishing pad according to this embodiment.

[0018] <<<Polishing pads>>> 1, polishing pad 10 is, for example, disc-shaped and includes polishing layer 11, cushion layer 12, and adhesive layer 13 for adhering polishing layer 11 and cushion layer 12. Polishing pad 10 includes cushion layer 12 and adhesive layer 13, but it is sufficient to include polishing layer 11, and it is not necessary to include cushion layer 12 and adhesive layer 13. Surface 10A of polishing pad 10 is surface 11A of polishing layer 11.

[0019] <<Polishing layer>> 2, the polishing layer 11 contains resin 11B and hollow particles 11C dispersed in the resin 11B. The thickness of the polishing layer 11 can be about 1 to 5 mm.

[0020] The polishing layer 11 has holes formed by the opening of the hollow particles 11C on the surface 11A of the polishing layer 11. The average opening diameter of the holes in the polishing layer 11 is preferably 5 μm or more and 20 μm or less. If the average opening diameter of the holes is 5 μm or more, a large amount of slurry can be held near the surface of the polishing layer 11 when the polishing object is polished. In addition, the polishing pad is scraped during polishing of the polishing object, generating polishing waste. However, if the average opening diameter of the holes is 20 μm or less, the variation in the partial elastic modulus of the hollow particles 11C can be further suppressed. The lower limit of the average opening diameter of the holes is more preferably 6 μm or more, 8 μm or more, or 10 μm or more, and the upper limit is more preferably 18 μm or less, 17 μm or less, or 15 μm or less. The average opening diameter can be measured by a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation).

[0021] The porosity of the holes on the surface 11A of the polishing layer 11 is not particularly limited, but is preferably 10% to 50%, more preferably 10% to 45%, and most preferably 10% to 40%. When the porosity is within the above-mentioned range, the retention of the slurry is good, and the polished object can be polished stably. Here, the porosity of the holes on the surface of the polishing layer means the ratio (%) of the total area of ​​the holes present on the surface to the area of ​​the surface of the polishing layer.

[0022] The number of pores, which is the number of pores per unit area present on the surface 11A of the polishing layer 11, is not particularly limited, but is preferably 1200 pores / mm 2 More than 2500 pieces / mm 2 If the number of openings per unit area is within the above numerical range, a large amount of slurry can be held near the surface 11A of the polishing layer 11, and the workpiece can be polished stably, thereby reducing the occurrence of scratches on the workpiece. 2 or more than 1600 pieces / mm 2 More preferably, the upper limit is 2200 pieces / mm 2 or less than 2000 pieces / mm 2 It is more preferable that the number of openings is equal to or less than 100. The number of openings can be measured by a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation).

[0023] The content of hollow particles 11C in the entire polishing layer 11 or the entire cured product of the curable composition for the polishing layer described below is not particularly limited, but is preferably 0.1% by mass or more and 10.0% by mass or less. If the content of hollow particles 11C is within the above numerical range, the density of the polishing layer 11 is made uniform. The lower limit of the content of hollow particles 11C is more preferably 0.5% by mass or more, or 1.0% by mass or more, and the upper limit is more preferably 5.0% by mass or less, or 4.0% by mass or less.

[0024] The density of the polishing layer 11 is not particularly limited, but is preferably 0.60 g / cm 3 More than 1.25g / cm 3 If the density is within the above range, the occurrence of scratches due to polishing by-products (polishing debris) can be reduced. The lower limit of the density of the polishing layer 11 is 0.65 g / cm 3 or more than 0.70g / cm 3 More preferably, the upper limit is 1.15 g / cm 3 or less than 1.10g / cm 3The following is more preferable: The density of the polishing layer 11 can be measured according to the procedures and conditions described in the section <Measurement of Density of Polishing Layer> in the Examples below.

[0025] The Shore D hardness of the polishing layer 11 is not particularly limited, but is preferably 35 or more and 75 or less. If the Shore D hardness is 35 or more, minor irregularities can be flattened, and if the Shore D hardness is 75 or less, the occurrence of scratches on the polished object can be reduced. The lower limit of the Shore D hardness of the polishing layer 11 is more preferably 40 or more, or 45 or more, and the upper limit is more preferably 70 or less, or 65 or less. The Shore D hardness of the polishing layer 11 can be measured based on the procedure and conditions described in the <Shore D hardness measurement of the polishing layer> section of the Examples described later.

[0026] <Resin> Resin 11B is not particularly limited, but for example, polyurethane resin is preferable. Polyurethane resin can be synthesized from polyisocyanate and polyol, and in particular, a reaction product of urethane prepolymer and hardener is preferable. Urethane prepolymer can be synthesized from polyisocyanate and polyol. Urethane prepolymer is preferably isocyanate-terminated urethane prepolymer having an isocyanate group at the end. Hereinafter, the structural unit derived from polyisocyanate, the structural unit derived from polyol, and the hardener constituting polyurethane resin will be described.

[0027] (Structural unit derived from polyisocyanate) The polyisocyanate-derived structural unit is not particularly limited, and examples thereof include alicyclic isocyanate-derived structural units, aliphatic isocyanate-derived structural units, and aromatic isocyanate-derived structural units. Among these, aromatic isocyanate-derived structural units are preferred, and 2,4-tolylene diisocyanate (2,4-TDI)-derived structural units are more preferred.

[0028] The alicyclic isocyanate is not particularly limited, but examples thereof include 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, and isophorone diisocyanate.

[0029] The aliphatic isocyanate is not particularly limited, but examples thereof include hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), tetramethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, trimethylene diisocyanate, and trimethylhexamethylene diisocyanate.

[0030] The aromatic isocyanate is not particularly limited, but examples thereof include phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), xylylene diisocyanate, naphthalene diisocyanate, and diphenylmethane-4,4'-diisocyanate (MDI).

[0031] (Structural unit derived from polyol) The structural unit derived from a polyol is not particularly limited, and examples thereof include a low molecular weight polyol having a number average molecular weight of less than 300 and a high molecular weight polyol having a number average molecular weight of at least 300. Among these, it is preferable to use at least a low molecular weight polyol, and it is preferable to use a low molecular weight polyol and a high molecular weight polyol in combination.

[0032] The number average molecular weights of the low molecular weight polyol and the high molecular weight polyol can be measured as polyethylene glycol / polyethylene oxide (PEG / PEO) molecular weights based on gel permeation chromatography (GPC) under the following conditions. <Measurement conditions> Column: Ohpak SB-802.5HQ (exclusion limit 10000) + SB-803HQ (exclusion limit 100000) Mobile phase: 5mM LiBr / DMF Flow rate: 0.3ml / min (26kg / cm 2 ) Oven: 60℃ Detector: RI 40℃ Sample volume: 20 μl

[0033] The low molecular weight polyol is not particularly limited, but examples thereof include low molecular weight polyols having two hydroxyl groups such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexane glycol, 2,5-hexanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecane dimethanol, and 1,4-cyclohexane dimethanol; and low molecular weight polyols having three or more hydroxyl groups such as glycerin, hexanetriol, trimethylolpropane, isocyanuric acid, and erythritol. The low molecular weight polyol may be used alone or in combination of two or more. Among these, the low molecular weight polyol is preferably a low molecular weight polyol having two hydroxyl groups, and more preferably diethylene glycol.

[0034] The polymer polyol is not particularly limited, but may be, for example, polyether polyol, polyester polyol, polycarbonate polyol, polyether polycarbonate polyol, polyurethane polyol, epoxy polyol, vegetable oil polyol, polyolefin polyol, acrylic polyol, and vinyl monomer modified polyol. The polymer polyol may be used alone or in combination of two or more. Among these, the polymer polyol is preferably polyether polyol, and more preferably polytetramethylene ether glycol.

[0035] The number average molecular weight of the polymer polyol is preferably 300-3,000, more preferably 500-2,500, and most preferably 850-2,000.

[0036] (hardening agent) The curing agent is not particularly limited, but may be, for example, a polyamine. The curing agent may be used alone or in combination of two or more kinds.

[0037] The polyamine is not particularly limited, but examples thereof include aliphatic polyamines such as ethylenediamine, propylenediamine, and hexamethylenediamine; alicyclic polyamines such as isophoronediamine and dicyclohexylmethane-4,4'-diamine; and aromatic polyamines such as 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. In addition, trifunctional triamine compounds and polyamine compounds having 4 or more functional groups can also be used. Among these, aromatic polyamines are preferred, and it is more preferred to use 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA).

[0038] <Hollow particles> The hollow particles 11C are particles having an outer shell and a cavity inside. The shape of the hollow particles 11C is not particularly limited, but may be, for example, spherical or approximately spherical.

[0039] The hollow particles 11C are dispersed in the resin 11B, but as shown in FIG. 2, the hollow particles 11C located on the surface 11A of the polishing layer 11 are open. When the elastic modulus is measured at 16,384 points in a 4 μm×4 μm region (hereinafter, this region may be referred to as the “measurement region”) of the inner bottom 11C1 of the open hollow particle 11C by an atomic force microscope (AFM) and an elastic modulus histogram with a class width of 2 GPa is created, the half-width of the peak of the approximation curve based on the elastic modulus histogram is 12 GPa or less. In this specification, the “peak” refers to a mountain-shaped portion when viewed as a whole of the approximation curve. In the case where there are multiple mountain-shaped portions in the approximation curve, the mountain-shaped portion with the highest frequency is referred to. In addition, in this specification, the “half-width” refers to the full width at half maximum. When measuring the elastic modulus with an atomic force microscope, the measurement is performed in the above measurement area, specifically, at 16384 points (128 x 128 points) within this area. Measurement with an atomic force microscope is performed in contact mode using a cantilever. That is, as shown in Figure 3, measurement with an atomic force microscope is performed while the probe 21 of the cantilever 20 is in contact with the inner bottom 11C1 of the hollow particle 11C located on the surface 11A of the polishing layer 11. The above approximation curve is obtained by connecting the midpoints of the upper sides of the bars indicating the frequency of each class in the elastic modulus histogram by spline interpolation.

[0040] The upper limit of the half-width of the peak is preferably 11 GPa or less, or 10 GPa or less. The smaller the half-width of the peak, the sharper the peak, so the more preferable it is, but the lower limit of the half-width of the peak may be 2 GPa or more.

[0041] The peak is preferably in the range of 1 GPa or more and 20 GPa or less. If the peak is 1 GPa or more, the hollow particles 11C are not too soft, so that minor irregularities on the polished object can be flattened, and if the peak is 20 GPa or less, the hollow particles 11C are not too hard, so that the occurrence of scratches on the polished object can be reduced. The lower limit of the peak is preferably 2 GPa or more, or 3 GPa or more, and the upper limit is preferably 17 GPa or less, or 15 GPa or less.

[0042] In the approximation curve, the frequency at the peak is preferably 2000 or more. If the frequency is 2000 or more, the variation in the elastic modulus is smaller, so that the occurrence of scratches on the polished object can be further reduced. The frequency is more preferably 2200 or more, or 2500 or more.

[0043] The approximation curve is preferably unimodal. In this specification, "unimodal" means that the approximation curve has one peak. When the approximation curve is unimodal, the local variation in the elastic modulus of the hollow particle 11C can be further suppressed.

[0044] The thickness of the outer shell of the hollow particles 11C dispersed in the resin 11B is not particularly limited, but is preferably 0.05 μm or more and 0.5 μm or less. If the thickness of the outer shell of the hollow particles 11C is 0.05 μm or more, the hollow particles 11C have a moderate elastic modulus, so that the workpiece can be stably polished. If the thickness of the outer shell of the hollow particles 11C is 0.5 μm or less, the variation in the partial elastic modulus of the hollow particles 11C is small, so that the occurrence of scratches on the workpiece can be further reduced. The lower limit of the thickness of the outer shell of the hollow particles 11C is more preferably 0.08 μm or more, or 0.1 μm or more, and the upper limit is more preferably 0.4 μm or less, 0.3 μm or less, or 0.2 μm or less. The thickness of the outer shell of the hollow particles 11C can be measured by a scanning electron microscope (SEM) (product name "JSM-5000LV", manufactured by JEOL Ltd.).

[0045] The material of the outer shell of the hollow particle 11C is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polyvinylpyrrolidone-based polymers, poly(meth)acrylic acid-based polymers, polyacrylamide-based polymers, polyethylene glycol-based polymers, polyhydroxyether acrylate-based polymers, polyethylene oxide-based polymers, polyurethane-based polymers, and acrylonitrile-based polymers. Among these, acrylonitrile-based polymers are preferred from the viewpoint of easily adjusting the half-width of the above-mentioned peak to 12 GPa or less. In addition, it is preferred that the material of the outer shell of the hollow particle 11C does not contain a polyvinylidene chloride-based copolymer such as a polyvinylidene chloride-acrylonitrile copolymer. Since the material of the outer shell of the hollow particle 11C does not contain a polyvinylidene chloride-based copolymer, it is easy to adjust the half-width of the above-mentioned peak to 12 GPa or less.

[0046] The polishing pad 10 is used to polish an object to be polished. The object to be polished is not particularly limited, but examples thereof include optical materials, semiconductor wafers, and glass substrates for hard disks.

[0047] <<Polishing pad manufacturing method>> Such a polishing pad 10 can be manufactured, for example, as follows: First, a prepolymer such as a urethane prepolymer, a curing agent, and unexpanded hollow particles are prepared.

[0048] The unexpanded hollow particles contain, for example, liquid hydrocarbons inside the outer shell. By heating the unexpanded hollow particles, the liquid hydrocarbons are vaporized, so that the hollow particles can be expanded and the particle size of the hollow particles can be increased.

[0049] There are expandable and non-expandable hollow particles. The expandable hollow particles can be controlled in particle size by heating, so that it is possible to obtain particles with a smaller particle size than the non-expandable hollow particles currently on the market. From this viewpoint, it is preferable to use expandable hollow particles. The average particle size (D 50The average particle diameter (D) of the hollow particles is not particularly limited, but may be about 1 μm or more and 20 μm or less before expansion. 50 ) can be measured using a laser diffraction particle size distribution measuring device (for example, product name "Mastersizer 2000" manufactured by Spectris Co., Ltd.).

[0050] Next, the prepolymer and hollow particles are mixed and kept at a temperature of 50° C. to 80° C. Meanwhile, the curing agent is kept at about 120° C. Here, the reason why the hollow particles are mixed with the prepolymer is that there is a risk that the hollow particles will expand due to heat if they are mixed with the curing agent.

[0051] Then, the prepolymer, the hollow particles, and the curing agent are mixed to obtain a curable composition for the polishing layer. The curable composition for the polishing layer is then fed into a mold and heated at a temperature in the range of 75°C to 140°C to expand the expandable hollow particles and cure the curable composition for the polishing layer. This produces a resin block, which is a cured product of the curable composition for the polishing layer.

[0052] The hardened resin block is removed from the mold and sliced ​​to a specified thickness to obtain the polishing layer. Then, grooves are formed on the surface of the polishing layer, and the layer is bonded to the cushion layer via an adhesive layer. Finally, the layer is cut into a disk shape. This produces a polishing pad.

[0053] According to this embodiment, when the elastic modulus is measured at 16,384 points within a 4 μm×4 μm region of the inner bottom 11C1 of the hollow particle 11C located on the surface 11A of the polishing layer 11 and an elastic modulus histogram with a class width of 2 GPa is created, the half-width of the peak of the approximation curve based on the elastic modulus histogram is 12 GPa or less, so that the variation in the partial elastic modulus of the hollow particle 11C is small. This reduces the variation in the contact pressure of the polishing pad 10 with the workpiece, thereby reducing the occurrence of scratches.

[0054] <<<Polishing equipment>>> The polishing pad 10 is incorporated into a polishing apparatus for use. The polishing apparatus 30 shown in FIG. 4 is a chemical mechanical polishing apparatus. The polishing apparatus 30 includes the polishing pad 10, a polishing platen 31 to which the polishing pad 10 is attached by a double-sided tape (not shown) or the like provided on the cushion layer 12 of the polishing pad 10, a holding platen 32 for holding the object to be polished 40, and a slurry supplying section 33 for supplying a slurry when polishing the object to be polished 40. The polishing pad 10 rotates together with the polishing platen 31 with the object to be polished 40 pressed against the surface 10A of the polishing pad 10, and polishes the object to be polished 40. At that time, a slurry is supplied from the slurry supplying section 33 between the polishing pad 10 and the object to be polished 40. The slurry is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the polishing effect is increased by the relative movement with the object to be polished 40 while the chemical components and abrasive grains in the slurry are flowing. The slurry is supplied to and discharged from the polishing surface through grooves or holes (not shown) provided in the polishing layer 11 . EXAMPLES

[0055] In order to explain the present invention in detail, the following examples are given, but the present invention is not limited to these. Fig. 5 is a photograph of the state in which the elastic modulus of the polishing layer of the polishing pad according to Example 1 is measured by an atomic force microscope (AFM), and Fig. 6 is a graph showing an approximation curve of the elastic modulus histogram obtained by measuring the elastic modulus of the polishing layer of the polishing pad according to Examples 1 and 2 and Comparative Example 1 by an atomic force microscope (AFM).

[0056] <Example 1> First, an isocyanate-terminated urethane prepolymer, a curing agent, and hollow particles (product number "Expancel (registered trademark) 044DU20", manufactured by Nippon Phillite Co., Ltd., shell: acrylonitrile-based polymer) were prepared. The isocyanate-terminated urethane prepolymer was obtained by reacting 2,4-tolylene diisocyanate (2,4-TDI), polytetramethylene ether glycol (PTMG650) having a number average molecular weight of 650, polytetramethylene ether glycol (PTMG1000) having a number average molecular weight of 1000, and diethylene glycol (DEG), and had an NCO equivalent of 460. 4,4-methylenebis(2-chloroaniline) (MOCA) was prepared as the curing agent. The hollow particles, Expancel (registered trademark) 044DU20, had an average particle size (D 50 ) is 7.7 μm, the expansion start temperature is 100 to 108°C, and the maximum expansion temperature is 143 to 160°C.

[0057] Next, the urethane prepolymer and the hollow particles were mixed in a mass ratio of 100:2.8, heated to 60°C, and defoamed under reduced pressure. The curing agent MOCA was dissolved at 120°C and defoamed under reduced pressure. Then, the urethane prepolymer: curing agent: hollow particles were mixed so that the mass ratio was 100:26.3:2.8. The resulting mixture was poured into a mold and cured primarily at 80°C for 30 minutes. The resin block containing the formed expanded hollow particles was removed from the mold and cured secondary at 120°C for 4 hours in an oven. The resulting resin block was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours. The resulting resin block was sliced ​​in a direction perpendicular to the thickness direction of the resin block to create a polishing layer with a thickness of 1.3 mm, and a double-sided tape was attached to the back side of this polishing layer to form a polishing pad.

[0058] <Example 2> In Example 2, a polishing pad was obtained in the same manner as in Example 1, except that hollow particles (product number "Matsumoto Microsphere (registered trademark) FN80GSD", manufactured by Matsumoto Yushi Kagaku Co., Ltd., outer shell: acrylonitrile-based polymer) were used instead of hollow particles (product number "Expancel (registered trademark) 044DU20", manufactured by Nippon Fillite Co., Ltd.). Matsumoto Microsphere (registered trademark) FN80GSD, which is a hollow particle, has an average particle size (D 50 ) of 7.1 μm, an expansion start temperature of 100 to 118°C, and a maximum expansion temperature of 125 to 160°C.

[0059] <Comparative Example 1> In Comparative Example 1, a polishing pad was obtained in the same manner as in Example 1, except that hollow particles (product number "Expancel (registered trademark) 461DU20", manufactured by Nippon Fillite Co., Ltd., outer shell: polyvinylidene chloride-acrylonitrile copolymer) were used instead of hollow particles (product number "Expancel (registered trademark) 044DU20", manufactured by Nippon Fillite Co., Ltd.). Expancel (registered trademark) 461DU20, which is a hollow particle, has an average particle size (D 50 ) of 7.2 μm, an expansion start temperature of 100 to 106°C, and a maximum expansion temperature of 143 to 151°C.

[0060] The formulations of the curable compositions for the polishing layer used in Example 1, Example 2, and Comparative Example 1 are shown in Table 1.

Table 1

[0061] <Elastic modulus measurement by AFM, elastic modulus histogram creation, and approximate curve acquisition> In the polishing layers of the polishing pads according to Examples 1 and 2 and Comparative Example 1, the elastic modulus of the hollow particles present on the surface of the polishing layer and having openings was measured using an atomic force microscope (AFM), and an elastic modulus histogram was obtained. Specifically, first, a sample piece having a size of 1 cm x 1 cm was taken from each polishing layer. Then, air was blown onto the sample piece to remove dust and the like adhering to the surface of the sample piece. After that, the sample piece was set in an atomic force microscope (product name "Park NX10", manufactured by Park Systems), and the height of the cantilever (product name "OMCL-AC160TS", manufactured by Olympus Corporation) was adjusted. Detailed information on the cantilever is described below. (Cantilever) Shape: rectangular Length: 160μm ·Resonance frequency: 300kHz Spring constant: 26N / m Material: Silicone ·Tip shape: square pyramid ·Tip height: 14μm ·Tip tip curvature: 7nm Probe material: Silicon

[0062] Next, the positions of the open-ended hollow particles on the surface of the sample were roughly identified using an atomic force microscope. As shown in Figure 5, the periphery of the hollow particles appears shiny due to the reflection of light, and this allowed the position of the hollow particles to be identified.

[0063] The elastic modulus was measured in contact mode by using an atomic force microscope to target the center of the inner bottom of the hollow particle. The measurement area was 4 μm × 4 μm, and the measurement points were 16,384 points (128 × 128 points). The probe was embedded in the sample until the load reached 250 nN, and then returned to its original position.

[0064] The elastic modulus of the inner base of the hollow particles was measured for two hollow particles for each sample piece using an atomic force microscope, and an elastic modulus histogram was created using the average value of the values ​​measured for the two hollow particles. An approximation curve for the elastic modulus histogram shown in Figure 6 was then obtained. This approximation curve was obtained by connecting the midpoints of the upper sides of the bars showing the frequency of each class in the elastic modulus histogram using spline interpolation.

[0065] From the obtained fitted curve, the peak position where the frequency was maximum, the full width at half maximum (FWHM) which is the width of the elastic modulus at 50% of the peak value, and the frequency at the peak position were each determined.

[0066] <Measurement of density of polishing layer> The density of the polishing layer was measured for the polishing pads of Examples 1 and 2 and Comparative Example 1. The density of the polishing layer (g / cm 3 ) was measured in accordance with the Japanese Industrial Standard (JIS K 6505:1995).

[0067] <Shore D hardness measurement of polishing layer> The Shore D hardness of the polishing layer was measured for the polishing pads of Examples 1 and 2 and Comparative Example 1. The Shore D hardness of the polishing layer was measured using a D-type hardness tester in accordance with the Japanese Industrial Standards (JIS K 6253-1 and 6253-3:2012). Here, the measurement sample was obtained by stacking multiple polishing layers as necessary so that the total thickness was at least 4.5 mm or more.

[0068] <Measurement of average pore size, pore ratio, and pore number> In the polishing layer of the polishing pad according to Examples 1 and 2 and Comparative Example 1, the average pore diameter, pore ratio, and the number of pores, which is the number of pores, of the holes in the polishing layer were measured. Specifically, three areas (each a rectangle of 0.5 mm long x 0.7 mm wide) were arbitrarily selected from the surface of the polishing layer without bias, and each area was observed at 400 times magnification using a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation). Each of the obtained images (rectangles of 0.5 mm long x 0.7 mm wide) was binarized using image processing software (software name "WinROOF2018 Ver4.0.2", manufactured by Mitani Shoji Co., Ltd.) to confirm the pores, and the circle equivalent diameter (pore diameter) was calculated from the area of ​​each pore. The cutoff value (lower limit) of the pore diameter was set to 5 μm, and noise components were excluded.

[0069] (Measurement of average pore diameter) All the pore diameters contained in each of the above regions (images) were averaged to calculate the average pore diameter for each region. The average pore diameters of the three regions thus obtained were further averaged to calculate the final average pore diameter.

[0070] (open area ratio) The ratio (%) of the total area of ​​holes per area of ​​each region (image) was calculated ((total area of ​​holes / area of ​​image (region)) × 100). The hole opening rates of the three regions thus obtained were further averaged to calculate the final hole opening rate.

[0071] (Number of openings) The number of apertures per area of ​​each of the above regions (images) (number / mm 2 The numbers of pores in the three regions thus obtained were then averaged to calculate the final number of pores.

[0072] <Measuring the thickness of the outer shell of hollow particles> In the polishing layer of the polishing pad according to Examples 1 and 2 and Comparative Example 1, the thickness of the outer shell of the hollow particles was measured. Specifically, three regions (each a rectangle of 0.5 mm long x 0.7 mm wide) were arbitrarily selected from the surface of the polishing layer without bias, and each region was observed at 2000 times magnification using a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.). In each image obtained, the hollow particles were confirmed, and the thickness of the outer shell of the hollow particles was manually measured at 10 points. Then, the thickness of the outer shell was calculated by averaging each thickness obtained in this way. The thickness of the outer shell of the three regions thus obtained was further averaged to calculate the final thickness of the outer shell.

[0073] <Polishing test> Using the polishing pads of Examples 1 and 2 and Comparative Example 1, polishing tests were carried out under the following polishing conditions.

[0074] (polishing conditions) Polishing machine used: F-REX300X (manufactured by Ebara Corporation) Disk: A188 (3M) Abrasive temperature: 20℃ Polishing platen rotation speed: 85 rpm Polishing head rotation speed: 86 rpm Grinding pressure: 3.5psi Polishing slurry (metal film): CSL-9044C (CSL-9044C stock solution: pure water = mixed solution of 1:9 by weight) (manufactured by Fujimi Corporation) Polishing slurry flow rate: 200ml / min Polishing time: 60 seconds Polished object (metal film): Cu film substrate (disc-shaped, 300 mm in diameter) Pad break: 35N 10 minutes Conditioning: Ex-situ, 35N, 4 scans

[0075] (Scratch evaluation) Using the polishing pads according to Examples 1 and 2 and Comparative Example 1, four Cu film substrates were polished under the above polishing conditions, and defects (surface defects) with a size of 150 nm or more were detected on the entire Cu film substrate after polishing using a high sensitivity measurement mode of a wafer surface inspection device (product name "Surfscan SP5", manufactured by KLA Tencor Corporation). For each detected defect, an SEM image taken using a review SEM was analyzed, and the defects were classified into "particles," "pad debris," and "scratches," and the number of scratches among them was counted. The results were the average value of the results obtained by polishing four Cu film substrates. Here, the classification "particles" refers to fine particles remaining on the surface of the substrate, the classification "pad debris" refers to debris of the polishing layer attached to the surface of the substrate, and the classification "scratches" refers to scratches on the surface of the substrate.

[0076] (polishing rate) Using the polishing pads according to Examples 1 and 2 and Comparative Example 1, the polishing rate of the polished substrate was measured under the above-mentioned polishing conditions as follows. First, the Cu film substrate before and after the polishing test was measured in the diameter direction on the Cu film substrate, and the thickness at those points before and after the polishing test was measured. Then, based on the measured thickness, the average thickness before the polishing test and the average thickness after the polishing test were calculated, and the average polished thickness was calculated by calculating the difference between these average values. Then, the polishing rate was calculated by dividing the obtained average polished thickness by the polishing time. The thickness was measured using a four-probe sheet resistance measuring device (product name "RS-200", manufactured by KLA Tencor Corporation, measurement: DBS mode).

[0077] The results are shown in Table 2. [Table 2]

[0078] As shown in Table 2, the polishing pad according to Comparative Example 1 had a half-width of 13 GPa, so the hollow particles had a large variation in the local elastic modulus and had a large number of scratches. In contrast, the polishing pads according to Examples 1 and 2 had a half-width of 12 GPa or less, so the hollow particles had a small variation in the local elastic modulus and had a small number of scratches. [Explanation of symbols]

[0079] 10...Polishing pad 10A…Surface 11...polishing layer 11A…Surface 11B…Resin 11C...Hollow particle 11C1…Inner bottom 12…Cushion layer 30...Polishing equipment

Claims

1. A polishing pad comprising a polishing layer, the polishing layer includes a resin and hollow particles dispersed in the resin; A polishing pad in which, when the elastic modulus is measured at 16,384 points using an atomic force microscope within a 4 μm x 4 μm area located on the surface of the polishing layer and at the inner bottom of the open hollow particle, and an elastic modulus histogram is created with a class width of 2 GPa, the half-width of the peak of the approximation curve based on the elastic modulus histogram is 12 GPa or less.

2. The polishing pad according to claim 1 , wherein the peak exists in the range of 1 GPa or more and 20 GPa or less.

3. 2. The polishing pad according to claim 1, wherein the frequency of the peak in the approximation curve is 2000 or more.

4. 2. The polishing pad according to claim 1, wherein the surface of the polishing layer has pores formed by openings in the hollow particles, and the pores have an average opening diameter of 5 μm or more and 20 μm or less.

5. The polishing pad of claim 1 , wherein the approximation curve is unimodal.

6. The polishing pad of claim 1 , wherein the resin comprises a polyurethane resin.

7. 2. The polishing pad of claim 1, wherein the hollow particles have an outer shell, the outer shell being free of polyvinylidene chloride based copolymers.

8. A polishing apparatus comprising the polishing pad according to claim 1 .

Citation Information

Patent Citations

  • Polishing pad, method of manufacturing the same, and method of manufacturing semiconductor device using the same

    JP7285613B2